KOLERASI PANJANG TUNGKAI DENGAN KECEPATAN LARI 40 METER PADA SISWA PUTRA DISEKOLAH DASAR - Siti Hijir (JURNAL PENDIDIKAN ROKANIA, 2017)
This action research is generally aimed to prove the relationship of limb length to running speed in grade 4 students of SD N 003 Rambah. The type of this research is correlation with the sample of fourth grade students of SD N 003 Rambah which amounts to 11 people with sampling using totalsampling.The data in this research were obtained from the measurement of leg length and 40 meter test run. Data analysis using product moment correlation and liliefors test for data normality test. After analyzed data obtained r value of 0.756 with rtabel = 0.632, it means rhitung = 0.756> rtabel = 0.632 and it can be said that there is a long leg with speed running 40 meters students of class IV SD Negeri 003 Pasir Pangaraian.